Dietary pattern and risk of hyperuricemia: an updated systematic review and meta-analysis of observational studies - Wen, Zhao-Yan; Wei, Yi-Fan; Sun, Ye-Huan; Ji, Wen-Ping (Frontiers in Nutrition, 2024)
The associations of posteriori dietary patterns with hyperuricemia (HUA) risk are contradictory. Several fair-quality observational studies with inconsistent results have been published following a prior review. Herein, we carried out an updated systematic review and meta-analysis to quantitatively analyze the aforementioned relationships.Methods: Our analysis protocol has been registered with PROSPEPO (Number: CRD42022376745). English publications were searched in Embase, PubMed, and Web of Science from inception to January 1, 2024. Summary odds ratio (OR) and 95% confidence intervals (CIs) were calculated by a random-effects model. We also conducted subgroup, sensitivity, and meta-regression analyses and publication bias assessments.Results: Thirteen studies with a total of 163,192 participants were included in current meta-analysis. Our finding revealed that plant-based pattern was linked with a 17% decreased risk of HUA (OR=0.83, 95%CI=0.72-0.94, I 2 =72.9%, n=10). There was no evidence of publication bias in the present analysis. The results of subgroup analyses were generally consistent with the main findings. In meta-regression analyses, no evidence of heterogeneity was detected in the subgroups. Furthermore, our analyses indicated that animal-based food pattern (OR=1.36, 95%CI=1.25-1.47, I 2 =26.7%, n=11) and sweet food pattern (OR=1.24, 95%CI=1.06-1.46, I 2 =0, n=2) was related to an increased risk of HUA.4 Conclusions: Plant-based pattern is inversely correlated with HUA risk, whereas animal-based food pattern and sweet food pattern is positively correlated with HUA risk.